Implementation of Virtual Reality Media with MilleaLab Platform in Computational Thinking Competence - Handoko, Dwi; Sutopo, Yeri; Qudus, Nur (Journal of Vocational and Career Education, 2024)
The advancement of digital technology requires sufficient computational cognitive skills, particularly in high school Computer Science subjects. However, there is a gap between these demands and the current computational thinking abilities of students, which remain relatively low. This study aims to develop effective learning media to enhance the computational cognitive skills of high school students in Computer Science subjects. The research method focuses on the development of virtual reality media using the Millealab platform, accessible through Android devices. The feasibility, practicality, and effectiveness of the media were tested through validation by media experts (Millealab) and subject matter experts (Computer Science teachers from SMAN 1 Cigombong), along with trials conducted with teachers. Results from the media expert validation showed an average score of 4.44 (highly feasible), while the subject matter expert received an average score of 3.57 (feasible). The practicality test conducted by users (teachers and students) resulted in an average score of 90.97% (highly practical). The effectiveness test, based on pretests and posttests, revealed a significant improvement in the cognitive performance of students. This study concludes that the developed virtual reality media is highly feasible, very practical, effective, and significantly improves the computational cognitive skills of students, especially in the computational thinking aspect of Computer Science. The development of comprehensive virtual reality-based learning media for Computer Science offers an innovative solution to address the gap in computational thinking abilities, providing an immersive learning experience and contributing positively to the quality of education.